2007
DOI: 10.1175/jcli4293.1
|View full text |Cite
|
Sign up to set email alerts
|

Surface Temperature and Humidity Trends in Canada for 1953–2005

Abstract: Annual and seasonal trends in temperature, dewpoint, relative humidity, and specific humidity are presented for the period 1953-2005. The analysis uses hourly observations from 75 climatological stations across Canada. Data were examined for discontinuities due to changes in instruments and observing practice. It was found that the main discontinuity corresponds to the replacement of the psychrometer by the dewcel in the early 1970s, which created an artificial negative step in relative humidity and dewpoint a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 21 publications
6
60
0
Order By: Relevance
“…4d). The significant decreasing trends in the number of days with wind chill are consistent with the significant increasing trends in winter mean temperature (Vincent et al, 2007) and significant decreasing trends in near-surface wind speed (Wan et al, 2010) observed mainly in western and southern regions of the country.…”
Section: Results a Trends In Extreme Heat Eventssupporting
confidence: 78%
See 2 more Smart Citations
“…4d). The significant decreasing trends in the number of days with wind chill are consistent with the significant increasing trends in winter mean temperature (Vincent et al, 2007) and significant decreasing trends in near-surface wind speed (Wan et al, 2010) observed mainly in western and southern regions of the country.…”
Section: Results a Trends In Extreme Heat Eventssupporting
confidence: 78%
“…There have been significant increases in HX > 35 and HX > 40 at fewer stations, and these are located mainly in southern Ontario. The significant increasing trends in the number of days with humidex are consistent with the significant increasing trends seen in summer mean temperature and summer mean dew point, mainly for locations in British Columbia and eastern regions of Canada (Vincent et al, 2007).…”
Section: Results a Trends In Extreme Heat Eventssupporting
confidence: 73%
See 1 more Smart Citation
“…As in situ observations of surface humidity can be easily influenced by changes of instruments and observation procedures (Dai, 2006), the simplified Clausius-Clapeyron equation (C-C equation) is recommended for practical convenience. Based on the C-C equation, the saturation vapour pressure over pure water will increase about 6.577gkg -1 , but global-scale and the regional-scale studies indicate that there are slight differences between in situ observations and theoretical values (Dai, 2006;Vincent et al, 2007;Brown et al, 2013). Hence, estimating the parameters of the formula is essential before analysing the trends of surface humidity at local scale.…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of brevity, in the discussion of the results 'hours per 51 years' are used, which implicitly means 'hours per year per 51 years'. The trends are presented over the 51-year period for compatibility with a previous cloud study (Milewska, 2004) and other related Canadian studies of trends in temperature, climate indices, and humidity that were performed for approximately the same time period (Zhang et al, 2000;Vincent and Mekis, 2006;Vincent et al, 2007).…”
Section: Introductionmentioning
confidence: 99%